The economic returns to nutrition-specific investments in Southern Asia and Africa South of the Sahara - Haile, Beliyou; Arndt, Channing; Ru, Yating; Alderman, Harold; Puett, Chloe (International Food Policy Research Institute, 2021)
Childhood undernutrition manifests itself in various ways including stunting, wasting, underweight, and micronutrient deficiencies. Stunting (being too short for the child’s age) captures a state of linear growth retardation and cumulative growth impairment due to chronic nutritional deficiency and illness that deprive a fetus and child of required nutrients. Despite the global decline in stunting prevalence by over 25% since 1990, an estimated 22% of the 150 million children are currently stunted with significant regional and within region disparity. Stunting is largely an irreversible outcome that stifles individuals from fulfilling their full development and economic potential. It increases the risk of impaired brain development with implications for cognitive and non-cognitive functions, educational performance, productivity, and chronic diseases later in life. It also increases the frequency and severity of exposure to common infections with one in seven under 5 deaths linked to it. Stunting and other forms of undernutrition costs countries billions of dollars in lost revenue and healthcare outlays. This report presents results from a cost benefit analysis (CBA) of a package of nutrition-specific investments studied as part of The Lancet Series on Maternal and Child Undernutrition and Copenhagen Consensus exercise. The investments tackle the immediate causes of child undernutrition ─ inadequate intake of nutrients, diseases, and infections and include behavior change communication programs to promote breastfeeding and complementary feeding; supplementation of crucial micronutrients to pregnant women and young children; provision of complementary foods to children; and management of severe acute malnutrition. We focus on two developing regions with the highest burden of stunting globally ─ Southern Asia and Africa South of the Sahara (SSA). Economic benefits are modelled for a cohort of children born between 2015 and 2030 who will join the workforce at 18 years of age and retire when 60 years old. Two benefit streams (the value of avoided premature child mortality and lifetime earnings gains) and two costs elements (the cost of the nutrition investments and of delivering schooling) are considered. Benefit-cost (BC) ratios are estimated under alternative scenarios based on the returns to stunting reductions and cost elements considered. Besides discount rates previously used in the nutrition and economics literature (between 3% and 6%), we consider a 10% discount rate used by the Millennium Challenge Corporation (MCC) for the sake of comparability of economic returns to these nutritional investments with that of other sectoral investments by MCC.